Jakość życia seksualnego młodych kobiet z stwardnieniem rozsianym - Lew-Starowicz, Zbigniew (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2013)
Sexuality and quality of life in young multiple sclerosis women is poorly known. Few studies indicate that sexual dysfunction can be found in the majority of patients. The most common are desire, arousal and orgasm disorders. The etiology of sexual dysfunctions is multifactorial. Sexual rehabilitation includes several methods that are also poory known and rarely implemented. (PNN 2013;2(3):104-108)